New semidominant mutations that affect mouse development. - Bogani, D; Warr, N; Elms, P; Davies, J; Tymowska-Lalanne, Z; Goldsworthy, M; Cox, R; Keays, D; Flint, J; Wilson, V; Nolan, P; Arkell, R (2004)
Dominantly acting mutations that produce visible phenotypes are frequently recovered, either during routine maintenance of colonies or from mutagenesis experiments. We have studied 12 dominant mouse mutations that cause a tail dysmorphology, a coat spotting phenotype, or a combination of these. The majority of these mutations act in a semidominant manner with the homozygous state associated with embryonic lethality and a visible phenotype at or before midgestation. The homozygous phenotypes include axis truncation and neural crest cell defects, as may be expected from the heterozygous phenotypes. The majority of mutations, however, also produced other phenotypes that include neural tube closure defects and aberrant heart looping. In one coat spotting mutant the homozygous condition is lethal before neural crest cell production commences. The mutated genes often function in processes additional to those alluded to by the heterozygous phenotype.